Distributional Effects of WTO Agricultural Reforms In Rich And Poor Countries - Hertel, Thomas W., 1953- 1953- (The World Bank, 2006)
Rich countries' agricultural trade policies are the battleground on which the future of the WTO's troubled Doha Round will be determined. Subject to widespread criticism, they nonetheless appear to be almost immune to serious reform, and one of their most common defenses is that they protect poor farmers. The authors' findings reject this claim. The analysis uses detailed data on farm incomes to show that major commodity programs are highly regressive in the United States, and that the only serious losses under trade reform are among large, wealthy farmers in a few heavily protected subsectors. In contrast, analysis using household data from 15 developing countries indicates that reforming rich countries' agricultural trade policies would lift large numbers of developing country farm households out of poverty. In the majority of cases these gains are not outweighed by the poverty-increasing effects of higher food prices among other households. Agricultural reforms that appear feasible, even under an ambitious Doha Round, achieve only a fraction of the benefits for developing countries that full liberalization promises, but protect U.S. large farms from most of the rigors of adjustment. Finally, the analysis indicates that maximal trade-led poverty reductions occur when developing countries participate more fully in agricultural trade liberalization